2012
DOI: 10.1364/oe.20.011153
|View full text |Cite
|
Sign up to set email alerts
|

Low loss silica hollow core fibers for 3–4 μm spectral region

Abstract: We describe a silica hollow-core fiber for mid-infrared transmission with a minimum attenuation of 34 dB/km at 3050 nm wavelength. The design is based on the use of a negative curvature core wall. Similar fiber designed for longer wavelengths has a transmission band extending beyond 4 µm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
241
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 395 publications
(247 citation statements)
references
References 21 publications
3
241
0
3
Order By: Relevance
“…At longer wavelengths of around 5.8 and 7.7 μm the losses were measured to be 30 and 50 dB/m, respectively. Transmission bands at 3.3 and 4.3 μm have a number of absorption peaks, which are related to the absorption lines of HCl (similar to work [3]) and atmospheric CO2, respectively. Optical absorption of fused silica glass is also shown for comparison ( Figure 5, black curve).…”
Section: Rfs With Touching and Non-touching Capillaries In A Claddingmentioning
confidence: 92%
See 2 more Smart Citations
“…At longer wavelengths of around 5.8 and 7.7 μm the losses were measured to be 30 and 50 dB/m, respectively. Transmission bands at 3.3 and 4.3 μm have a number of absorption peaks, which are related to the absorption lines of HCl (similar to work [3]) and atmospheric CO2, respectively. Optical absorption of fused silica glass is also shown for comparison ( Figure 5, black curve).…”
Section: Rfs With Touching and Non-touching Capillaries In A Claddingmentioning
confidence: 92%
“…In doing so, the capillaries can either touch each other (Figure 7a), or between the capillaries can be inserted additional elements at the beginning and at the end of the preform (Figure 7b). In the first case, a RF with touched capillaries [1] or an "ice-cream-cone" structure [3] is obtained. In the second case, it is possible to obtain a RF with non-touching capillaries [4].…”
Section: Technology Of the Silica Glass Based Rfmentioning
confidence: 99%
See 1 more Smart Citation
“…OLLOW antiresonant fibers (ARF) are emerging as attractive candidates for low-loss light guidance at near and mid-infrared wavelengths [1,2]. Their low optical nonlinearity and ultralow fraction of power carried in the glass result in a high damage threshold for ultrashort pulse delivery applications, while also placing less stringent demands on the transparency of the materials employed [3].…”
Section: Introductionmentioning
confidence: 99%
“…In Kagome-type hollow core fibers with a hypocycloid core surround, several studies have shown a dependency between the leakage loss of the fiber and its cladding structure [4,5], and recent works have already established that leakage loss can be significantly reduced when the curvature of the arcs forming the core boundary is increased [6][7][8], although no clear physical explanation has been provided for this behavior. A more recent family of hollow antiresonant fibers, already highlighted for its low loss in the infrared [2] and for its relatively low bending loss at large mode field diameters [5], consists of a simpler design in which the air-core is surrounded by a number of touching or non-touching circular capillaries [1,9]. These fiber types offer a better platform to try to understand the effect that the curvature of the membranes surrounding the core has on the overall loss, since different curvatures can be obtained while keeping unchanged key geometrical parameters [5,10].…”
Section: Introductionmentioning
confidence: 99%